RMSG Implementation Respiratory Muscle Stretch Gymnastic (RMSG) to Extend Inspiratory and Expiratory Periods in Dyspnea Patients - Lukman, Muhammad Nasril; Subandi, Andi (Jurnal Pinang Masak, 2024)
Dyspnea is a subjective sensation of shortness of breath. The emergency nursing problem that arises in dyspnea is ineffective breathing patterns. Ineffective breathing patterns are inspirations and/or expirations that do not provide adequate ventilation. Patients with ineffective breathing patterns are given airway management interventions, in addition to providing oxygen therapy to maximize oxygen entering the body, by providing the Respiratory Muscle Stretch Gymnastics (RMSG) breathing movement technique to help loosen the respiratory muscles to normalize the patient's breathing pattern. At the assessment stage, data was obtained on a case of dyspnea, namely COPD, with complaints of shortness of breath for three days but worsened on the day he was taken to the emergency room with the patient having an irregular breathing pattern, rapid pulse and a history of hypertension. Based on this assessment, a nursing diagnosis of ineffective breathing pattern was obtained with a nursing plan for 1x3 hours. The nursing plan that will be given is airway management with Respiratory Muscle Stretch Gymnastics (RMSG) therapeutic measures. The results of the analysis show that Respiratory Muscle Stretch Gymnastics (RMSG) is not appropriate to carry out in the emergency room where this action is less able to overcome ineffective breathing patterns in dyspnea patients in the emergency room.